Promoter hypermethylation of mismatch repair genes, hMLH1 and hMSH2 in oral squamous cell carcinoma. - Czerninski, R; Krichevsky, S; Ashhab, Y; Gazit, D; Patel, V; Ben-Yehuda, D (My University, 2009)
Major risk factors of oral squamous cell carcinoma (OSCC) are environmental and can lead to DNA mutagenesis. Mismatch repair (MMR) system functions to repair small DNA lesions, which can be targeted for promoter hypermethylation. We therefore wanted to test whether hypermethylation of MMR genes (hMLH1, hMSH2) could contribute to oral carcinogenesis by correlating the information to patient clinical data.